1996
DOI: 10.1038/bjc.1996.378
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced paracellular barrier function of rat mesothelial cells partially protects against cancer cell penetration

Abstract: Summary To study pathophysiological roles of mesothelial barrier functions in protection against cancer cell invasion, we isolated mesothelial cells from the rat abdominal cavity and cultured them with 10-6M all-transretinoic acid (RA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Endothelial cells form a continuous monolayer in vivo and act as a selective barrier to the passage of small molecules, proteins, and the extravagation of inflammatory cells and cancer cells in blood vessels (Satoh et al, 1996;Tobioka et al, 1996;Hoover et al, 1998;Kleeff et al, 2001;Hoevel et al, 2002;Soderholm et al, 2002). The function of tight junction can be regulated by agents, including cytokines.…”
mentioning
confidence: 97%
“…Endothelial cells form a continuous monolayer in vivo and act as a selective barrier to the passage of small molecules, proteins, and the extravagation of inflammatory cells and cancer cells in blood vessels (Satoh et al, 1996;Tobioka et al, 1996;Hoover et al, 1998;Kleeff et al, 2001;Hoevel et al, 2002;Soderholm et al, 2002). The function of tight junction can be regulated by agents, including cytokines.…”
mentioning
confidence: 97%
“…Cancer metastasis proceeds by a series of steps, among which the capacity of cancer cells to invade surrounding normal tissues is of central importance in the dissemination of disease (13). The interaction between cancer and mesothelial cells lining the cavity is crucial for achieving the complex sequence of cancer cell dissemination into the body cavity.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of the submesothelial invasion of cancer cells, the TJs of the mesothelial cells can function as a defence against the invasion of cancer cells. Likewise, TJs are also a defense barrier against endothelial invasion (both in intravasation and extravasation), as they are known to work as a barrier to the paracellular passage of cells and substances between the epithelial or endothelial cells (13). Metastasis is the primary cause of fatality in breast cancer Although there are believed to be numerous events contributing to the process of metastasis, it is widely accepted that the loss of cell-cell adhesion in the neoplastic epithelium is necessary for the invasion of the surrounding stromal elements and subsequent metastatic events (14).…”
Section: Introductionmentioning
confidence: 99%
“…These findings support our previous observation that all-transretinoic acid-induced functional tight junctions in mesothelial and endothelial cells play a key role in giving rise to resistance to cancer cell invasion. 29,30) This study suggests that HNF-4α may regulate cancer cell transmigration via not only activation of the Fas-FasL system, but also by modulation of the expression of previously undefined target genes. Alternatively, Tanaka et al reported that FasL is rapidly cleaved from the membrane by a metalloproteinase to become a soluble form (sFasL), 47) and that sFasL inhibits Fas-mediated lymphocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…28) We have previously demonstrated that enhanced paracellular barrier function in mesothelial and rat lung endothelial (RLE) cells induced by treatment with all-trans-retinoic acid leads to significant resistance to cancer cell invasion. 29,30) Considering these results together with the fact that retinoid receptors directly regulate expression of the HNF-4α gene through binding to the retinoic acid response element (RARE), 31,32) we hypothesized that expression of HNF-4α-target genes in endothelial cells might prevent invasion of cancer cells. Since our preliminary data suggested that HNF-4α induced FasL expression in endothelial cells in vitro, in the light of recent evidence implicating apoptosis and gene regulation in the control of tumor behavior, we were led to consider the potential role of HNF-4α in the endothelium for tumor responses to apoptosis-inducing factors in the microenvironment.…”
mentioning
confidence: 99%